Social science approaches to infodemiology: understanding the social, political, and economic context of information. (September 2022) - Cole, Jennifer; Tulloch, Olivia; Schmidt-Sane, Megan; Hrynick, Tabitha; Ripoll, Santiago
Embedded within the COVID-19 pandemic is the spread of a new pandemic of information – some accurate, some not – that can challenge the public health response. This has been termed an 'infodemic' and infodemic management is now a major feature of the World Health Organization's work on health emergencies. This commentary highlights political, social, and economic aspects of infodemics and posits social science as critical to mitigating the current infodemic and preventing future ones. Infodemic managers should address the wider context of infodemics if we are to understand narratives, help to craft positive ones, and confront the root causes of misinformation rather than just the symptoms.